Дефектні структури діоксиду титану як каталітичні центри - Smirnova, O. S.; Grebenyuk, A. G.; Lobanov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
The spatial and electronic structures of defect and admixture sites of titania polymorphs have been analysed in the article as well as their manifestations in adsorption, catalysis, and photocatalytic processes. The role has been examined of the various forms of adsorbed oxygen in the redox reactions involving TiO2 surfaces. The results of experimental studies known from the literature are compared the properties of molecular and periodic models for the titania bulk and surface evaluated by means of quantum chemical methods.